Adolescent Pregnancy in the Dominican Republic - World Bank (World Bank, Washington, DC, 2021)
Over the past several decades, robust economic growth and sustained poverty reduction have made the Dominican Republic (DR) a regional success story, yet the country’s adolescent pregnancy rate remains far above the average for Latin America and the Caribbean (LAC) and is closer to the levels observed in Sub-Saharan Africa (SSA). Adolescent pregnancy poses severe risks to girls and young women, including elevated rates of maternal1 and child mortality, and is strongly correlated with sexual abuse and domestic violence. This report analyzes the DR’s persistently high rate of adolescent pregnancy, identifies its main determinants and consequences, and evaluates the effectiveness of policies and programs designed to help reduce adolescent pregnancy and mitigate its adverse personal and social impacts. This report presents a set of stylized facts on adolescent pregnancy in the DR and uses an econometric model to estimate the statistical significance of risk factors for adolescent pregnancy and its negative effects at the individual and household levels. Finally, an assessment of early adolescent versus late adolescent pregnancy reveals important differences in their causes and implications.